Penerapan Laporan Keuangan Berbasis SAK EMKM sebagai Alat Evaluasi Kinerja Keuangan Perusahaan: Studi Kasus pada UMKM Marning Siung Mas, Desa Gabru Kecamatan Gurah, Kabupaten Kediri - Jerina Shinta Devi; Akhmad Naruli; Ninik Anggraini (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the application of SAK EMKM as a financial performance evaluation tool in Marning Siung Mas MSMEs, Gabru Village, Gurah District. It focuses on how SAK EMKM improves financial report quality and performance evaluation through liquidity, solvency, and profitability ratios. Using a descriptive method with qualitative and quantitative approaches, the study compiles financial statements based on SAK EMKM, including journals, ledgers, adjustments, and financial reports such as profit and loss and financial position. The results show that Marning Siung Mas MSMEs have not fully implemented SAK EMKM standards. Although production costs are calculated systematically, selling prices are still based on market rates. The financial ratio analysis reveals a Current Ratio of 486% (healthy), a Debt to Equity Ratio of 13.9% (healthy), and a Return on Assets of 19.8% (unhealthy). This indicates that the company maintains strong liquidity and capital structure but has not yet managed its assets effectively to generate optimal profits.